Student satisfaction measurement in higher education - Verra Syahmer; Rahmat Nurcahyo; Djoko S. Gabriel; Ellia Kristiningrum (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2022)
Since the quality of academic services can affect students’ satisfaction, identification of academic quality attributes is needed. It is divided into several factors using factor analysis and modeling the relationship between academic quality and students’ satisfaction using the multiple regression method. This research used primary data obtained from questionnaires given to undergraduate students of Universitas Indonesia. The results showed six factors affecting students’ satisfaction. However, only two of them, i.e. the lecturers’ abilities to deliver learning materials and the quality of the classroom and building, were significant. The top priority factor was the lecturers’ abilities to deliver learning materials.